2015
DOI: 10.1126/science.aab0673
|View full text |Cite
|
Sign up to set email alerts
|

CHO-bearing organic compounds at the surface of 67P/Churyumov-Gerasimenko revealed by Ptolemy

Abstract: The surface and subsurface of comets preserve material from the formation of the solar system. The properties of cometary material thus provide insight into the physical and chemical conditions during their formation. We present mass spectra taken by the Ptolemy instrument 20 minutes after the initial touchdown of the Philae lander on the surface of comet 67P/Churyumov-Gerasimenko. Regular mass distributions indicate the presence of a sequence of compounds with additional -CH2- and -O- groups (mass/charge rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
96
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(109 citation statements)
references
References 23 publications
9
96
2
2
Order By: Relevance
“…It is the precursor for the formation of many of the complex organic molecules (COMs) observed in the ISM, both in the gas and the solid phases; molecules that subsequently became incorporated into cometary ices during the formation of planetary systems, with some believed to lead to the formation of prebiotic molecules responsible for the chemical origins of life [1][2][3][4] . CH 3 OH has been observed in comets [5][6][7] and on the surfaces of Trans-Neptunian objects [8][9][10] , that are believed to be preserved from the primordial cloud and planetary accretion disk that formed our Solar System. In dense molecular clouds, from which stars are formed, CH 3 OH is observed to be one of the most abundant constituents of ices after H 2 O and CO [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…It is the precursor for the formation of many of the complex organic molecules (COMs) observed in the ISM, both in the gas and the solid phases; molecules that subsequently became incorporated into cometary ices during the formation of planetary systems, with some believed to lead to the formation of prebiotic molecules responsible for the chemical origins of life [1][2][3][4] . CH 3 OH has been observed in comets [5][6][7] and on the surfaces of Trans-Neptunian objects [8][9][10] , that are believed to be preserved from the primordial cloud and planetary accretion disk that formed our Solar System. In dense molecular clouds, from which stars are formed, CH 3 OH is observed to be one of the most abundant constituents of ices after H 2 O and CO [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to COSAC's mass spectral interpretation, Wright et al (2015) concluded that CO 2 was the major contributor to the m/z 44 and 45 peaks measured by Ptolemy. Acetaldehyde, formamide and acetamide are comparatively less volatile than CO 2 and could possibly be a constituent species of the subsurface cometary grains that probably entered the COSAC vent tubes immediately after impact excavation.…”
Section: Discussionmentioning
confidence: 58%
“…Results were published by Wright et al (2015) and Morse et al (2015). In the latter paper the authors consider the temporal evolution of three abundant cometary species: H 2 O, CO and CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Initiated either in the ice phase (Colangeli et al 2004;Cottin et al 1999;Meinert et al 2012Meinert et al , 2016Strazzulla and Palumbo 1998;Vinogradoff et al 2013) or in the gaseous phase in the protosolar nebula (Nuth et al 2008), complex organic compounds are observed in carbonaceous chondrite (Martins 2011), micrometeorites, UltraCarbonaceous Antarctic micrometeorites (UCAMMs) and interplanetary dust particles (IDPs) (Clemett et al 1993;Dartois et al 2013;Matrajt et al 2013) and in comets (Capaccioni et al 2015;Elsila et al 2009;Goesmann et al 2015;Wright et al 2015;Fray et al 2016). The surfaces of comets, asteroids, and their fragments (i.e.…”
Section: Small Bodies and Exogeneous Sources Of Organic Compounds mentioning
confidence: 99%
“…High energy processes in the surface of those planetary bodies may break molecular bonds, leading to new molecular rearrangements and new molecular species, or to the destruction of the organic content of the object. Recent data from the Rosetta comet rendezvous mission show a large number of organic molecules, in particular those containing N and O on the surface (Goesmann et al 2015;Wright et al 2015). A study of the stability of organic species in a relevant space environment is crucial to constrain the amount of organic material that might have been imported to the primitive Earth, especially on small particles such as IDPs in which the organic content is much less protected from radiations than in the larger bodies where only the surface is affected by radiation (Muñoz Caro et al 2006).…”
Section: Small Bodies and Exogeneous Sources Of Organic Compounds mentioning
confidence: 99%